Orientia tsutsugamushi: The dangerous yet neglected foe from the East - Anwesha Banerjee; Smita Kulkarni (Elsevier, 2021)
Orientia tsutsugamushi (OT), the causative agent of the vector-borne Scrub typhus zoonotic disease in humans, is a unique microorganism that exists in the Asia-Pacific region since a long time. In spite of its occurrence, the organism had been neglected until recent years. Humans are the accidental dead-end hosts of O. tsutsugamushi and display manifestations which are both severe and misleading. The vast antigenic diversity of OT and non-pathognomic symptoms of Scrub typhus, create hurdles in the clinical management of the disease and impede the OT-research. Many countries in the Asia-Pacific region have reported the resurgence of OT- infections and have raised concerns for its expanding distribution. This has triggered the development of advanced techniques for diagnosis and research on exploring a successful vaccine candidate to reduce the burden of the disease. Thus, the aim of this systematic review is to provide an update on the recent advances in the OT-research and highlight the key areas that have remained obscure and demand attention.